Optical ages on loess derived from outwash surfaces constrain the advance of the Laurentide Ice Sheet out of the Lake Superior Basin, USA. Issue 2 (March 2014) - Schaetzl, Randall J.; Forman, Steven L.; Attig, John W.
Abstract: We present textural and thickness data on loess from 125 upland sites in west-central Wisconsin, which confirm that most of this loess was derived from the sandy outwash surfaces of the Chippewa River and its tributaries, which drained the Chippewa Lobe of the Laurentide front during the Wisconsin glaciation (MIS 2). On bedrock uplands southeast of the widest outwash surfaces in the Chippewa River valley, this loess attains thicknesses > 5 m. OSL ages on this loess constrain the advance of the Laurentide ice from the Lake Superior basin and into west-central Wisconsin, at which time its meltwater started flowing down the Chippewa drainage. The oldest MAR OSL age, 23.8 ka, from basal loess on bedrock, agrees with the established, but otherwise weakly constrained, regional glacial chronology. Basal ages from four other sites range from 13.2 to 18.5 ka, pointing to the likelihood that these sites remained geomorphically unstable and did not accumulate loess until considerably later in the loess depositional interval. Other OSL ages from this loess, taken higher in the stratigraphic column but below the depth of pedoturbation, range to nearly 13 ka, suggesting that the Chippewa River valley may have remained a loess source for several millennia.